Opportunities and challenges for commercial encryption applications in the Internet of Vehicles - Li, Yuning; Li, Kaitian; Zhang, Xiuli (International Journal of Global Economics and Management, 2024)
The rapid development of vehicle networking technology has brought broad opportunities for commercial encryption applications, but it is also accompanied by many challenges. As an important guarantee for the information security of the Internet of vehicles, commercial encryption applications have obtained significant development opportunities in terms of technological innovation, market demand and policy support. However, the commercial encryption applications of connected vehicles are also facing challenges such as technical difficulties, lack of standardization, and increasing security threats. This paper aims to deeply analyze the opportunities and challenges of the commercial encryption application of the Internet of vehicles, and put forward corresponding development suggestions, in order to provide reference for the security development of the Internet of vehicles industry.